Effectiveness of Scratch-based interactive learning media on students' mathematical problem-solving - Hidayatul Maqhfiroh; Hevy Risqi Maharani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Mathematical problem-solving ability is a fundamental skill essential for students’ academic success and real-world challenges. This study aims to design a Scratch-based educational game, "Aritmashop," as a learning medium to enhance students’ mathematical problem-solving skills, particularly in social arithmetic. Using the R&D (Research and Development) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 33 eighth-grade students from SMPN 1 Kalinyamatan. Data were collected through validation sheets (media and material experts), teacher/student questionnaires, and problem-solving tests. Results demonstrated that "Aritmashop" met validity, practicality, and effectiveness criteria, with students responding positively to its interactive design, engaging material presentation, and conceptual clarity. This research contributes to mathematics education by providing an empirically validated digital tool that bridges abstract concepts with real-world applications through gamified learning. The findings affirm that Scratch-based games like "Aritmashop" can significantly support mathematics instruction. The study concludes that technology-based educational games such as "Aritmashop" can be a viable and effective solution to improve students’ motivation and mathematical problem-solving abilities in the classroom. This research contributes to mathematics education by offering a theoretically grounded and empirically validated gamified learning tool that integrates technology into the curriculum, enhancing both student engagement and conceptual understanding.